Managing the farmscape for connectivity increases conservation value for tropical forest-dependent birds - dataset - Estrada-Carmona, Natalia (2019)
We assessed species mobility for five neotropical bird species with distinct life history characteristics representing an affinity gradient for forest habitat. We used seven years of mist-netting data for estimating species habitat affinity and for predicting species mobility using the Circuitscape model across a 4,371 ha farmscape in Costa Rica. Circuitscape allowed us to estimate changes in movement probability, relative changes in resistance that species experience during dispersal (measured as resistance distance and passage area through which species can move) under four farmscape management scenarios. The four land-use scenarios included: (a) the 2011 farmscape land-use composition and configuration, b) converting all existing live fences to post-and-wire fence lines in the farm (c) converting simplified coffee agroforests to multistrata coffee agroforests in the farm, and d) placing multistrata live fences around the perimeter of evey parcel and roads in the farm. The dataset includes the digitized land uses using a 2010 GeoEye image with a 0.46 m resolution at 1:1500 m scale. We ground-truthed the farmscape in August-September 2011 to validate the digitized land use map, and constructed four alternative management scenarios to estimate the impacts of on-farm practices on species mobility.